(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study analyzes modern approaches to using herbal preparations in the treatment and prevention of periodontitis. It provides insights into the advantages of phytotherapy, including antimicrobial, anti-inflammatory, and regenerative properties. Additionally, the study examines the chemical composition and effectiveness of medicinal plants such as Polygonum hydropiper and Urtica dioica in periodontal disease management.